“TOO MANY COOKS IN THE KITCHEN? EU-NATO OVERLAP IN SAFEGUARDING EUROPEAN CRITICAL ENERGY INFRASTRUCTURE POST - 2022” (Security Dialogues, 2024)
Until 2022, European citizens had not faced any direct physical threat to theirCritical Energy Infrastructure (CEI) for generations. However, in September of that year,everything changed with the sabotage of the Nord Stream 1 and 2 pipelines, which connectedGermany to Russia. The research begins from this period due to the significance of boththe year and the event. That year saw the outbreak of the conflict in Ukraine, introducing anew (in)security landscape for Europe. The event was also unprecedented, emphasizing theimportance of this starting point. This shifted CEI protection to a top priority for both theEU and NATO, prompting action from both international organizations to prevent similarincidents in the future. However, the October 2023 Balticconnector incident — damage to anunderwater gas pipeline and communication cable between Finland and Estonia — revealedinefficiencies in the synergy between NATO and the EU regarding CEI protection. This raisedthe research question: is there any overlap between the two organizations in CEI protection,and if so, in which areas?Through an in-depth case study using the analytical tool of organizational overlap, it wasfound that there is significant overlap between the EU and NATO in their efforts to protectEuropean CEI, particularly in the areas of division of labor and mandate. The study examinedtheir strategies, discourse, methods, and intentions, concluding that coordination remainsinsufficient. Although steps have been taken to address the issue—such as the creationof the EU-NATO Task Force on CEI resilience and the “Coherent Resilience 2023 Baltic”tabletop exercise—progress in 2024 remains limited, leaving much to be desired from bothorganizations in this field.